Development of the universal model of mechatronic system with a hydraulic drive - Panchenko, Anatolii; Voloshina, Angela; Kiurchev, Sergey; Titova, Olena; Onopreychuk, Dmytro; Stefanov, Volodymyr; Safoniuk, Ivan; Pashchenko, Viktor; Radionov, Hennadii; Golubok, Maksim (Eastern-European Journal of Enterprise Technologies, 2018)
The growing demands to performance of mechatronic systems with a hydraulic drive of movable operating elements of self-propelled machines require application of new approaches to the process of their development and design. Functional parameters of the mechatronic systems depend on a rational choice of operating modes of the hydraulic system and the design implementation of the mechatronic modules of these systems. Quality of the mechanically driven mechatronic system is largely determined by its dynamic characteristics. In order to improve dynamic characteristics, a universal model describing dynamic and static processes occurring in the elements of the mechatronic system was proposed. The pump, the hydraulic motor, the safety valve and the working fluid are considered interrelated as a single whole. The universal model takes into account peculiarities of functioning and mutual influence of all elements of the mechatronic system as well as the features of the working fluid and can be used with any hydraulic machines of a volumetric action. The study of dynamics of the changes in functional parameters of the mechanically driven mechatronic system was carried out for four stages of its operation: acceleration of the hydraulic drive (triggering of the safety valve); valve closure; completion of acceleration and steady-state operation. The conducted studies have established that when activating the hydraulic drive of the mechatronic system from the moment of the safety valve activation and to its closure, operating conditions do not affect changes in the functional parameters. In the steady-state operation, there are fluctuations caused by unevenness of the pump feed and load fluctuations. It should also be noted that the mechatronic system with a hydraulic motor having larger working volume has better dynamic characteristics than that with smaller working volume.